2008
DOI: 10.1177/021849230801600110
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Replacement in Severe Pulmonary Arterial Hypertension

Abstract: The immediate postoperative hemodynamics in 43 patients with severe pulmonary arterial hypertension who underwent mitral valve replacement between January 2000 and September 2001 were studied prospectively. The mean age was 30.6 years. There was mitral stenosis in 19 (44.1%), mitral regurgitation in 9 (20.9%), and mixed lesions in 15 (34.9%). In 36 patients (83.7%, group 1) pulmonary arterial pressure was sub-systemic, with a mean of 58.1 mm Hg and pulmonary vascular resistance of 743.4 dyne x s x cm(-5). Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 11 publications
4
28
0
4
Order By: Relevance
“…However, there is no consensus about the outcome of patients with PAH after MVR in the literature, some studies have revealed that severe PAH is associated with poorer outcome and higher mortality rate [3][4][5][6][7][8] while some others do not agree with this and believed that severe PAH do not imply the greater risk in corrective surgery; [9][10][11][12][13][14][15][16][17][18][19] but the point is that the definition of PAH varies across studies, pulmonary artery pressure >40, 50, 70 and 110 have been considered as severe PAH in various studies. [9][10][11][12][13][14][15][16][17][18][19] To our knowledge, there is no related study about this issue in Iran, and most of the previous, related works are not so recent [5][6][7][8][12][13][14][15][16][17][18][19] and had been conducted with a small sample size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus about the outcome of patients with PAH after MVR in the literature, some studies have revealed that severe PAH is associated with poorer outcome and higher mortality rate [3][4][5][6][7][8] while some others do not agree with this and believed that severe PAH do not imply the greater risk in corrective surgery; [9][10][11][12][13][14][15][16][17][18][19] but the point is that the definition of PAH varies across studies, pulmonary artery pressure >40, 50, 70 and 110 have been considered as severe PAH in various studies. [9][10][11][12][13][14][15][16][17][18][19] To our knowledge, there is no related study about this issue in Iran, and most of the previous, related works are not so recent [5][6][7][8][12][13][14][15][16][17][18][19] and had been conducted with a small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] To our knowledge, there is no related study about this issue in Iran, and most of the previous, related works are not so recent [5][6][7][8][12][13][14][15][16][17][18][19] and had been conducted with a small sample size. A major proportion of related studies has assessed the late outcome of MVR in patients with severe PAH.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there is no consensus in the literature on the results after surgery for this category of patients; Some studies have associated PAH with a poor outcome and an estimated high mortality rate of 31% [1], which has led some authors to consider PAH as an absolute contraindication to MVR [5][6][7][8][9], while others do not fully agree and argue that severe PAH does not imply a greater surgical risk [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…(22) Mitral valve replacement should still be offered, albeit with a higher risk, even in the presence of severe pulmonary hypertension as long as pulmonary pressures are below systemic pressure. (23) MiTrAl vAlvE rEplAcEMEnT…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%